Eksistensi Wisata Kuliner pada Masa Pandemi Covid-19 dalam Pemulihan Ekonomi dan Pariwisata di Desa Sangeh, Badung, Bali - Waruwu, Dermawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
This article discussed the existence of culinary tourism during the Covid-19 pandemic in economic recovery and tourism in Sangeh Village, Badung, Bali. The tourism sector as a source of income for the Balinese people and a contributor to foreign exchange for the country has decreased during the Covid-19 pandemic. Almost all culinary tourism spots in Bali are closed because tourist visits have decreased significantly during the Covid-19 pandemic. The existence of culinary tourism in Sangeh Tourism Village has actually increased tourist visits. This article is a descriptive study that analyzed the types, forms, and marketing strategies of culinary tourism during the Covid-19 pandemic in restoring the economy and tourism in Sangeh Tourism Village. This study used a qualitative approach through observation, interviews, and documentation. The writer interviewed business owners and tourists who had a culinary tour in the village. The results of the study showed: First, the types of culinary tourism sold by the Sangeh Tourism Village are in the form of food and drinks favored by young people such as coffee, meatballs, and burgers. Second, the existence of culinary tourism in Sangeh Tourism Village provides a relatively cheap price to reach young people. Third, the culinary tourism marketing strategy in Sangeh Tourism Village uses social media that is often used by young people such as Facebook, Instagram, and Twitter. The results of this study provided information about the existence of culinary tourism during the Covid-19 pandemic by targeting young people using social media and providing relatively cheap prices while enjoying the rural atmosphere in Sangeh Tourism Village.